2007
DOI: 10.4049/jimmunol.179.11.7852
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Chronic Murine Colitis by Peptide-Mediated Transduction of the IκB Kinase Inhibitor NEMO Binding Domain Peptide

Abstract: The NF-κB family of transcription factors is a central regulator of chronic inflammation. The phosphorylation of IκB proteins by the IκB kinase (IKK) complex (IKKα, IKKβ, and NF-κB essential modulator or NEMO) is a key step in NF-κB activation. Peptides corresponding to the NEMO binding domain (NBD) of IKK blocks NF-κB activation without inhibiting basal NF-κB activity. In this report, we determined the effects of the IKK inhibitor peptide (NBD) in a model of spontaneously occurring chronic murine colitis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…These findings are consistent with those of previous studies characterising the in vitro NF-κB blocking effect of different NBD peptide sequences in cytokine-stimulated mononuclear cells, osteoclasts and fibroblasts [26,[35][36][37][38]. Remarkably, NBD peptide reversed the cellular responses induced by long-term exposure to HG, but did not influence either NF-κB or cell viability under normoglycaemic conditions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies characterising the in vitro NF-κB blocking effect of different NBD peptide sequences in cytokine-stimulated mononuclear cells, osteoclasts and fibroblasts [26,[35][36][37][38]. Remarkably, NBD peptide reversed the cellular responses induced by long-term exposure to HG, but did not influence either NF-κB or cell viability under normoglycaemic conditions.…”
Section: Resultssupporting
confidence: 92%
“…Remarkably, NBD peptide reversed the cellular responses induced by long-term exposure to HG, but did not influence either NF-κB or cell viability under normoglycaemic conditions. Hence, the primary role of NF-κB in normal cellular functions is preserved, resulting in less toxicity, which represents an advance over other NF-κB inhibitors [18,19,35]. Our results constitute the first in vivo characterisation of the nephroprotective effect of NBD peptide.…”
Section: Resultsmentioning
confidence: 67%
“…Recent studies have reported the use of NBD peptide therapy for the treatment of colitis and arthritis in mouse models without any evidence of toxicity [22,61]. Similarly, in the present study, we did not identify any toxicity as a result of treatment of NBD peptide, including any lethality or acute and chronic effects on behavior after daily injection of NBD peptide up to 500 µg per mouse.…”
Section: Nbd Peptide Treatment Showed No Evidence Of Drug Induced Toxsupporting
confidence: 66%
“…NF-κB was found to be activated in mucosal cells of IBD patients [16], while pharmacological inhibition of NF-κB activity ameliorated intestinal inflammation in mouse models of colitis. For instance, administration of antisense oligonucleotides to p65 or a peptide that binds to NEMO and inhibits IKK activation reduced the severity of colon inflammation in both chemical-induced models and in the Il-10 -/-mouse model of colitis [17][18][19]. These studies suggested that excessive NF-κB activation contributes to intestinal inflammation and that NF-κB inhibition could have therapeutic effects in IBD.…”
Section: Detrimental Role For Nf-κb Activation In the Intestinementioning
confidence: 97%